2008
DOI: 10.1097/jto.0b013e318189f526
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Ground-Glass Opacity (GGO) Lesions–Large Size and a History of Lung Cancer are Risk Factors for Growth

Abstract: After initial management and 3 month follow-up, larger size (more than 10 mm) and a history of lung cancer are risk factors for GGO growth, and therefore should be considered when making a follow-up plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
103
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 23 publications
13
103
2
1
Order By: Relevance
“…Thus, the majority of pure GGNs remained stable on later follow-up. On the other hand, in study populations, which included patients with a history of malignancy, a much higher proportion (15%-58%) of pure GGNs showed interval growth (42,43). These studies indicate that a history of past malignancy is a risk factor for nodule growth.…”
Section: Natural Clinical Course Of Subsolid Nodulesmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, the majority of pure GGNs remained stable on later follow-up. On the other hand, in study populations, which included patients with a history of malignancy, a much higher proportion (15%-58%) of pure GGNs showed interval growth (42,43). These studies indicate that a history of past malignancy is a risk factor for nodule growth.…”
Section: Natural Clinical Course Of Subsolid Nodulesmentioning
confidence: 90%
“…For part-solid GGNs, growth was observed in 40%-46.2% after a mean or median follow-up period of 35-59 months (41,42). In a study population from the Multicentric Italian Lung Detection (MILD) project, Silva et al (41) disclosed the natural course of part-solid GGNs with a solid component smaller than 5 mm.…”
Section: Natural Clinical Course Of Subsolid Nodulesmentioning
confidence: 99%
“…Although the natural history and growth rate of the various lesions along the adenocarcinoma spectrum have been previously studied (6,7,(22)(23)(24)(25), to the best of our knowledge, there are no published studies in which the volume and mass changes of pulmonary adenocarcinomas with GGOs (and their respective DTs) have been investigated using 3D software for each CT performed throughout follow-up (not just the baseline and last CT scan). Therefore, this study aimed to explore the growth pattern and rate of a group of pulmonary adenocarcinomas appearing as GGOs that were retrospectively analyzed with 3D commercial software to further understand their natural volumetric behavior.…”
mentioning
confidence: 99%
“…Because biopsy of these lesions is sometimes difficult, these slowgrowing small GGO lesions are currently considered to be candidates for observation rather than for definitive diagnosis or treatment [11]. Hiramatsu et al reported that some independent factors affecting the growth rates of GGO lesions include the initial tumor size and the history of lung cancer [8]. However, in our case, the mean doubling time of multiple GGO lesions was 402 days, and the shortest doubling time was 255 days, being shorter than that reported in the past.…”
Section: Discussionmentioning
confidence: 99%